The Influence of Warehouse Capability, Inventory Management, and Human Resource Competence on the Effectiveness of Warehouse Management Mediated by Supply Chain Optimization (A Case Study of Aluminium and Ferronickel Warehouses at PT Sinergi Mitra Lestari) - Muhammad Andrey Alfian; Erna Mulyati; Maniah Maniah (Dinasti Publisher, 2025)
PT Sinergi Mitra Lestari Indonesi is a company engaged in the management and distribution of mining products, particularly tin and ferronickel. In its business operations, the company relies on warehouse performance as a central hub for controlling the flow of goods and information. This study seeks to identify and empirically analyze how warehouse capability, inventory management, and human resource competence contribute to the effectiveness of tin and ferronickel warehouse management at PT Sinergi Mitra Lestari Indonesia. Furthermore, the study explores how the effectiveness of warehouse management impacts the optimization of the company’s supply chain. Employing a quantitative approach, data were collected through questionnaires distributed to 229 respondents consisting of the warehouse staff, logistics personnel, and management level. This data is subsequently analyzed using the SEM-PLS method to analyze both direct and indirect relationships among variables. Furthermore, supply chain optimization significantly mediates the relationships between these independent variables and warehouse management outcomes, emphasizing its crucial role in translating operational capabilities into performance improvements. Among the predictors, warehouse capability demonstrates the strongest total effect on management effectiveness, highlighting the importance of infrastructure and technological support in logistics operations. This shows that PT Sinergi Mitra Lestari Indonesia must enhance warehouse efficiency, optimize space utilization, and strengthen supply chain processes to remain competitive in the mining sector.